WATER RESISTANCE OF RECYCLED PAPER PANEL - Rani Suryandono, Alexander; Wihardyanto, Dimas (Department of Architecture, Universitas Tanjungpura, 2017)
Recycled paper has many benefits, from saving woods to reducing carbon footprints. Industrialized recycled paper were mainly made in developed countries. These processes are using high technology and utilize chemical reactions and materials that can only be done in large factories. Meanwhile, paper are also used in developing countries. Newspaper is one of the mass medias that use a high number of paper. Printed newspaper are still used by the majority of people which they prefer rather than the digital newspaper version. This paper focuses in newspaper recycling that can be done in a home industry without high technology involved so that the people of developing countries could easily do it. The paper is broken into cellulose and then glued using tapioca starch. The recycled paper is formed as a panel for partition in a house. The recycled panel paper is put into the water to measure the resistance level. This experiment will help to understand the recycled panel paper strength against water. Recycling process in a home industry can be a part of green solution, especially in paper use. Through this experiment method research, it can be seen that recycled paper panel has a certain resistance level from water and may be used for partition panel. Keywords: recycled paper, panel, partition, environmental friendly, building materials Â KETAHANAN AIR PANEL KERTAS DAUR ULANGKertas daur ulang memiliki banyak manfaat, mulai dari mengurangi penggunaan kayu sampai karbon. Industri kertas daur ulang banyak terdapat di Negara maju. Proses ini membutuhkan teknologi tinggi dan menggunakan reaksi dan bahan kimia yang hanya mungkin dilakukan di pabrik besar. Sementara itu, kertas juga digunakan di Negara berkembang. Koran adalah satu dari media massa yang menggunakan banyak kertas. Koran cetak masih lebih banyak digunakan daripada media online. Paper ini membahas daur ulang kertas koran yang dapat dilakukan pada skala rumah tangga tanpa teknologu tinggi sehingga dapat dilakukan oleh orang awam di negara berkembang. Kertas koran dihancurkan menjadi selulosa dan menggunakan tepung tapioca sebagai perekat. Kertas daur ulang dibentuk menjadi panel untuk digunakan sebagai dinding partisi. Panel kertas daur ulang ini dimasukkan kedalam air untuk mengetahui ketahan terhadap air. Percobaan ini memperlihatkan tingkat ketahanan panel kertas daur ulang terhadap air. Proses daur ulang yang dapat dilakukan pada rumah tangga dapat menjadi bagian dari solusi hijau, khususnya pada penggunaan kertas. Melalui riset berbasis eksperimen ini, dapat dilihat bahwa panel kertas daur ulang memiliki ketahanan terhadap air dan dapat digunakan sebagai dinding partisi. Kata-kata kunci: kertas daur ulang, panel, partisi, ramah lingkungan, bahan bangunanÂ REFERENCESAlice Wisler (2015) Facts about Recycling Paper. http://greenliving.lovetoknow.com/Facts_About_Recycling_Paper. Accessed 2 April 2016 Clay Miller (2011) 5 Benefits of Recycling Paper. http://www.ways2gogreenblog.com/2011/09/28/5-benefits-of-recycling-paper/. Accessed 10 May 2016 Hari Goyal (2015) Grades of Paper. http://www.paperonweb.com/grade.htm. Accessed 2 April 2016 Hari Goyal (2015) Properties of Paper. http://www.paperonweb.com/paperpro.htm. Accessed 2 April 2016 Kathryn Sukalich (2016) Everything You Need to Know about Paper Recycling. http://earth911.com/business-policy/business/paper-recycling-details-basics/. Accessed 15 July 2016 [U1] Larry West (2015) Why Recycle Paper. http://environment.about.com/od/recycling/a/The-Benefits-Of-Paper-Recycling-Why-Recycle-Paper.htm. Accesed 15 June 2016 Marie-Luise Blue (2008) The Advantages of Recycling Paper. http://education.seattlepi.com/advantages-recycling-paper-3440.html. Accessed 15 June 2016 Nina Spitzer (2009) http://www.sheknows.com/home-and-gardening/articles/810025/the-impact-of-disposable-coffee-cups-on-the-environment. Accessed 15 June 2016 Radio New Zealand (2010) Iwi not Giving Up Fight against Tasman Mill Discharges. http://www.radionz.co.nz/news/regional/64521/iwi-not-giving-up-fight-against-tasman-mill-discharges. Accessed 15 July 2016 Rick LeBlanc (2016) Paper Recycling Facts, Figures and Information Sources. https://www.thebalance.com/paper-recycling-facts-figures-and-information-sources-2877868?_ga=1.192832942.544061388.1477446686. Accesed 2 April 2016 Robinson Meyer (2016) Will More Newspapers Go Nonprofit? http://www.theatlantic.com/technology/archive/2016/01/newspapers-philadelphia-inquirer-daily-news-nonprofit-lol-taxes/423960/. Accessed 3 August 2016 School of Engineering at Darthmouth (2010) Forest and Paper Industry. http://engineering.dartmouth.edu/ d30345d/courses/engs171/Paper.pdf. Accessed 2 April 2016 T. Subramani, V. Angappan. (2015). Experimental Investigation of Papercrete Concrete. International Journal of Application or Innovation in Engineering and Management. Volume 4 Issue 5 page 134-143